1997
DOI: 10.1200/jco.1997.15.9.3111
|View full text |Cite
|
Sign up to set email alerts
|

p53 expression and cell proliferation as prognostic factors in laryngeal squamous cell carcinoma.

Abstract: Overexpression of p53 is associated with favorable disease-free and overall survival in laryngeal squamous cell carcinoma. It may also have an independent prognostic value in laryngeal cancer. M/V index, p53 overexpression, and stage predict with significant accuracy the 10-year overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
59
2
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 45 publications
0
59
2
2
Order By: Relevance
“…In laryngeal SCC, Jin et al 29 reported that p53 overexpression was an independent prognostic factor for poor disease-free survival. In contrast, Hirvikoski et al 30 showed a favorable clinical outcome in patients with p53 overexpression. There are several reports showing no association between p53 overexpression and prognosis in laryngeal carcinoma [26][27][28] and in oral cancer.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In laryngeal SCC, Jin et al 29 reported that p53 overexpression was an independent prognostic factor for poor disease-free survival. In contrast, Hirvikoski et al 30 showed a favorable clinical outcome in patients with p53 overexpression. There are several reports showing no association between p53 overexpression and prognosis in laryngeal carcinoma [26][27][28] and in oral cancer.…”
Section: Discussionmentioning
confidence: 86%
“…Some studies showed no correlation, 19,26 -28 whereas others showed a significant correlation between p53 expression and prognosis. 21,29,30 Conversely, a majority of studies showed an association of p53 mutation with poor prognosis, 20,31 but some studies showed that there is no association between p53 mutation and prognosis. 19 Overexpression of bcl-x has been reported to protect tumor cells from apoptosis, 32 whereas increased bax expression promotes apoptosis induced by cytotoxic drugs and radiation.…”
mentioning
confidence: 99%
“…The fraction of positive tumour cells was primarily analysed in a continuous scale but, for statistical calculations, the percentage distribution of p21 and AP-2 was divided into two groups using median as a cut-off level: ² 10%, > 10%, ² 30%, > 30% respectively. Finally, the percentage distribution of p53 was scored as previously: ² 20%, > 20% (Hirvikoski et al, 1997).…”
Section: Immunohistochemistry and Detection Of P21 P53 And Ap-2mentioning
confidence: 99%
“…In recent years, investigations on the importance of certain genetic and immunological markers (p53, Ki67, BNIP3, TGM2, and IGF1R) have begun. [7][8][9][10][11][12] The aim of this study was to determine the prognostic factors which have an impact on the treatment, in addition to side effects and survival rates in patients with larynx cancer.…”
mentioning
confidence: 99%